THE PHONEME AS A BASIC-LEVEL CATEGORY: EXPERIMENTAL EVIDENCE FROM ENGLISH - Mompean Gonzalez, Jose A. (International Journal of English Studies, 2009)
This paper presents the results of a concept formation experiment that provides evidence on the possible existence of a basic-level of taxonomic organization in phonological categories as conceived of by phonetically naïve, native speakers of English. This level is roughly equivalent to the phoneme as described by phonologists and linguists. The reason why the phoneme could be considered as the basic level of taxonomies of phonological categories is discussed.